Stilistika-Fonologi Qira’at Abu Ja’far: Studi Bacaan Ikhfa’ Kha’ dan Ghain - Sunarto Sunarto (Bulletin of Indonesian Islamic Studies, 2022)
This paper identifies one of Abu Ja'far's rules of ushul qira’at, namely reading ikhfa' if there is a consonant nun or a tanwin meeting with kha' or ghain. This reading is unique and distinctive considering that the majority of qurra' agree that the two letters are idzhar letters, not ikhfa'. By using stylistic-phonology as a tool in interpreting, it is concluded that the polemic is rooted in the different descriptions of makhraj and, there are those who categorize both of them as part of the letter khalqiyyah or throat, and some include it as part of the letter located at the base of the tongue. This difference has implications for how to read when meeting with a consonant nun or tanwin. The next implication of reading ikhfa' kha' and ghain in Abu Ja'far's qira’at is to present the harmony of sounds that are displayed in several verses. The sound is also not only a sweetener in the work of recitation, but also as a supporter of the meaning to be conveyed by the verse.